Controlling Effects of Residual Deformation on Pore Pressure: A Loess Soil Case - Kun Liu; Lanmin Wang; Wentong Tian; Zhenming Wang; Na Li; Yu Sun; Junjie Sun (Shock and Vibration)
What the role of each phase medium plays and how their interactions do work should be essential problems to understand dynamic behaviours of soils. In order to disclose interactions between solid, water, and air phases of soils, we applied loess samples to analyse controlling effects of residual deformation on pore pressure based on three kinds of laboratory tests. We obtained the similarity and difference of mechanical behaviors of soil samples under different water contents and loading. Both process and cause of pore air/water pressures are independent of initial stress conditions or loadings. However, absolute values of pore water pressure depend on the confining pressure, whereas the pore air pressure is contrary. The uniformity of responding process and cause of pore pressure depend upon the interaction mechanism between solid particles and air/water media, but the different absolute values depend upon the permeability and compressibility of air/water.